Immunotherapy of uveal melanoma: vaccination against cancer : Multicenter adjuvant phase 3 vaccination study using dendritic cells laden with tumor RNA for large newly diagnosed uveal melanoma - Schuler-Thurner, Beatrice; Bartz-Schmidt, K. -U.; Bornfeld, N.; Cursiefen, C.; Fuisting, B.; Grisanti, S.; Heindl, L. M.; Holbach, L.; Keserue, M.; Knorr, H.; Koch, K.; Kruse, Friedrich; et al. (Ophthalmologe, 2015)
Uveal melanomas are the most common malignant tumors of the eye. With modern molecular biological diagnostic methods, such as chromosome 3 typing and gene expression analysis, these tumors can be categorized into highly aggressive (monosomy 3, class II) and less aggressive forms. This molecular biological stratification is primarily important for determining the risk of these tumors as no therapy is currently available that is able to prevent or delay metastases. A randomized study of patients with a poor prognosis (monosomy 3) is currently being carried out in order to determine whether a cancer vaccine prepared from autologous (patient's own) dendritic cells and uveal melanoma RNA can prevent or delay progression and further metastases of this extremely aggressive form of cancer. Inclusion in the uveal melanoma study, which hopes to provide a potential therapeutic option for patients, is only possible if patients are referred to an institution that is able to manufacture and provide this vaccination before the patient is operated on or treated with radiation. Untreated tumor material is necessary for producing the vaccine on an individualized patient basis.
EVALuna2:19521